1951
DOI: 10.1515/bchm2.1951.287.1-6.195
|View full text |Cite
|
Sign up to set email alerts
|

Über die antibiotische Wirkung der Flechtenstoffe

Abstract: Über die antibiotische Wirkung einzelner Flechtensäuren ist gleichzeitig von Barry, Stoll und Mitarb., J. Klosa und Marshak 1 berichtet worden. Burgholder und Evans 2 berichteten über die antibiotische Wirkung einiger Flechtenextrakte und hoben hervor, daß ihre antibiotische Wirkung nicht bleibend ist, sondern inaktiviert wird. V art i a 3 untersuchte 82 Flechtenarten und konnte aus 22 die Usninsäure gewinnen. Einige der untersuchten Flechtenarten zeigten keine antibiotische Wirkung, obwohl sie nach den chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1952
1952
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…These experiments showed that lichen compounds did not inhibit gram-negative rods or fungi at concentrations of Յ32 g/ml (data not shown) but were active against staphylo-cocci, enterococci, and anaerobic bacteria (Tables 1 and 2), confirming earlier qualitative data (3,6,7,12,15)…”
supporting
confidence: 85%
See 1 more Smart Citation
“…These experiments showed that lichen compounds did not inhibit gram-negative rods or fungi at concentrations of Յ32 g/ml (data not shown) but were active against staphylo-cocci, enterococci, and anaerobic bacteria (Tables 1 and 2), confirming earlier qualitative data (3,6,7,12,15)…”
supporting
confidence: 85%
“…In two strains of enterococci, a 98% inhibition of growth was seen at 16 g/ml for both optic antipodes; in staphylococci, only 65% inhibition of growth was achieved. Stoll et al (15) reported a bacteriostatic effect against staphylococci but a bactericidal effect against Mycobacterium tuberculosis in vitro (7,15), which could not be confirmed in experiments in animals by other investigators (8).…”
mentioning
confidence: 89%
“…Previously, various biological activities of usnic acid and usimines A -C were reported. Usnic acid was isolated from several species of lichens and showed several biological activities such as antitumour (Kupchan and Kopperman, 1975), antibacterial (Klosa, 1953;Lauterwein et al, 1995), antimycobacterial (Ingólfsdóttir et al, 1998), analgesic and antipyretic (Okuyama et al, 1995), antiviral , antiproliferative (Kumar and Müller, 1999) and anti-infl ammatory. Usimines A -C from R. terebrata showed moderate inhibitory activity against the therapeutically targeted protein tyrosine phosphate 1B (PTP1B) (Seo et al, 2008).…”
Section: Antibacterial Activities Of the Isolated Compoundsmentioning
confidence: 99%
“…There is fairly good agreement between the present results and those of Evans (1944), with the exception of the present finding of squamatic acid. Squamatic acid is only seen reported for C. bacillaris in Klosa (1951).…”
Section: Discussionmentioning
confidence: 98%